New-onset versus relapsing giant cell arteritis treated with tocilizumab: 3-year results from a randomized controlled trial and extension - Stone, John H.; Spotswood, Helen; Unizony, Sebastian H.; Aringer, Martin; Blockmans, Daniel; Brouwer, Elisabeth; Cid, Maria C.; Dasgupta, Bhaskar; Rech, Jürgen; Salvarani, Carlo; Spiera, Robert; Bao, Min (Rheumatology, 2021)
Objective. Tocilizumab plus prednisone induces sustained glucocorticoid-free remission in patients with GCA. However, its long-term benefits in new-onset vs relapsing disease are uncertain, and the value of weekly vs everyother-week dosing has not been evaluated.
CRIS-Team WoS Importer:2022-05-13